A Literary Study On Sandhigata Vata – A Brief Review Study - Rameshwari; Ojha, Aruna; Sahu, Jeevan Lal (International Research Journal of Ayurveda & Yoga, 2021)
Sandhigata vata (osteoarthritis) etiopathogenesis and symptomatology are described in succinct form in the Ayurvedic classics. In modern science, the diagnosis of Sandhigata vata mentioned in the classical texts is clinically similar to the condition of osteoarthritis. Sandhigata vata (osteoarthritis) is mentioned in all of the Samhitas and Sangraha Grantha’s under Vata vyadhi. Both Dhatus (body tissues) experience Kshaya (depletion) in Vriddhavastha, thereby leading to Vata Prakopa and making individuals vulnerable to many diseases. Sandhigata vata can be associated with degenerative joint disorder or with osteoarthritis, which, in essence, renders the patient as crippled as possible, extends and decreases the person’s overall operating ability. It prohibits regular tasks such as walking, washing, bathing, etc., thereby rendering people disabled.